Effects of dexmedetomidine on pharyngeal swallowing and esophageal motility—A double‐blind randomized cross‐over study in healthy volunteers. Issue 1 (2nd December 2022) - Cajander, Per; Omari, Taher; Magnuson, Anders; Scheinin, Harry; Scheinin, Mika; Savilampi, Johanna
Abstract: Background: Sedative agents increase the risk of pulmonary aspiration, where an intact swallowing function is an important defense mechanism. Dexmedetomidine is an α2 ‐adrenoceptor agonist widely used during procedural sedation due to beneficial properties with minimal respiratory effects. The effects of dexmedetomidine on pharyngeal swallowing and esophageal motility are not known in detail. Methods: To determine the effects of dexmedetomidine on pharyngeal swallowing and esophageal motility, nineteen volunteers were included in this double‐blinded, randomized placebo‐controlled cross‐over study. Study participants received target‐controlled dexmedetomidine and placebo infusions. Recordings of pressure and impedance data were acquired using a manometry and impedance solid‐state catheter. Data were analyzed from three bolus swallows series: baseline, during dexmedetomidine/placebo infusion at target plasma concentrations 0.6 ng ml −1 and 1.2 ng ml −1 . Subjective swallowing difficulties were also recorded. Key Results: On pharyngeal swallowing, dexmedetomidine affected the upper esophageal sphincter with decreased pre‐ and post‐swallow contractile pressures and an increase in residual pressure during swallow‐related relaxation. On esophageal function, dexmedetomidine decreased contractile vigor of the proximal esophagus and increased velocity of the peristaltic contraction wave. Residual pressures during swallow‐related esophagogastric junction (EGJ) relaxation decreased, as did basal EGJ resting pressure. The effects on the functional variables were not clearly dose‐dependent, but mild subjective swallowing difficulties were more common at the higher dose level. Conclusions and Inferences: Dexmedetomidine induces effects on pharyngeal swallowing and esophageal motility, which should be considered in clinical patient management and also when a sedative agent for procedural sedation or for manometric examination is to be chosen. Abstract : Dexmedetomidine, like other sedatives, induces effects on pharyngeal swallowing and esophageal motility, which should be taken into account in clinical patient management and also when a sedative agent for procedural sedation or for manometric examination is to be chosen.